Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2024
DOI: 10.1017/s2045796024000088
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of mental health diagnoses during the COVID-19 pandemic: a multinational network study

Yi Chai,
Kenneth K. C. Man,
Hao Luo
et al.

Abstract: Aims Population-wide restrictions during the COVID-19 pandemic may create barriers to mental health diagnosis. This study aims to examine changes in the number of incident cases and the incidence rates of mental health diagnoses during the COVID-19 pandemic. Methods By using electronic health records from France, Germany, Italy, South Korea and the UK and claims data from the US, this study conducted interrupted time-series analyses to compare the monthly incident cases and the incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Despite reports of increased anxiety symptoms during the pandemic, these did not translate to a major rise in mental health service use. Studies, including one using NHIS data, found minimal changes in mental health service use, in line with the findings of a recent multinational study showing an initial decrease in mental health diagnoses during the pandemic, followed by a gradual recovery …”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Despite reports of increased anxiety symptoms during the pandemic, these did not translate to a major rise in mental health service use. Studies, including one using NHIS data, found minimal changes in mental health service use, in line with the findings of a recent multinational study showing an initial decrease in mental health diagnoses during the pandemic, followed by a gradual recovery …”
Section: Discussionsupporting
confidence: 77%
“…Studies, including one using NHIS data, 37 found minimal changes in mental health service use, in line with the findings of a recent multinational study showing an initial decrease in mental health diagnoses during the pandemic, followed by a gradual recovery. 38 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation